Lifelong Learning and Web 2.0 Tools: Online Study Circles for Supporting Active Learning and Citizenship - Simándi, Szilvia (Pedagogika, 2018)
Thanks to the spreading of technological devices, as well as Internet services (Web 2.0), the areas and possibilities of lifelong learning and education have broadened nowadays. This article concerns the practical implementation of lifelong learning. Our assumption is that today there is also a possibility to inspire study circles in the online study environment with the involvement of community sites. The basis of this can also be given by a common topic of interest, and we analyze this as a study field of those people who cannot find the way to meet personally and who wish to study in their free time in a community (cf. lifelong learning, Longworth, 2001).We examine the opportunities of online study circles within the confines of a SWOT analysis. In this connection, one of our empirical examinations was aimed at studying the personal experience and views of students engaged in online study circles. At the same time, we also examined the possibilities of participant-centered methods that can be used in study circles (for example, project work). In the present study, we are going to select from the results of our empirical work carried out among students who study adult education (n = 103).